Finnish Feed Tables and Nutrient Requirements : Ruminants, pigs, poultry, horses - Kuoppala, Kaisa; Vattulainen, Jenni; Perttilä, Sini; Saastamoinen, Markku; Rinne, Marketta (Luonnonvarakeskus, 2024)
The Finnish Feed Tables and Nutrient Requirements 2024 publication contains the feed values used in Finland, the basis for their calculation and the nutrient requirements of cattle, sheep, goats, pigs, poultry and horses. The main objective of the Feed Tables is to present as reliable feed values as possible that describe the relative differences in the production responses of feeds when used in animal nutrition. The composition and feed values for reference feeds are based on extensive Finnish and international research data and long-term work. According to the Feed Act in Finland, the energy and protein values of feed materials in Finland must be based on the calculation criteria published by the Natural Resources Institute Finland. Feed values and nutrient requirements are an entity that provides the basis for ration formulation for animals to optimize diets based on animal requirements and feed prices. Up-to-date information on feed values and nutrient requirements is available on the Feed Tables web service (www.luke.fi/feedtables), which also has a Finnish (www.luke.fi/rehutaulukot) and a Swedish (www.luke.fi/fodertabeller) version. Feed values and nutrient requirements are an important basis for ration formulation of different livestock groups, and we hope that they will contribute to the health and welfare of animals and the economic sustainability of livestock production, reduce the environmental burden of livestock production and ensure quality animal products in the food chain.
Keywords: amino acid; energy value; cattle; chicken; composition; concentrate feed; feed; feed value; feed material; feeding; forage; goat; horse; mineral; pig; poultry; protein value; reference feed; ruminant; sheep; vitamin